Optimized PID tuning for the automatic control of neuromuscular blockade - Merigo, L.; Padula, Fabrizio; Latronico, N.; Mendonça, T.; Paltenghi, M.; Rocha, P.; Visioli, A. (2018)
© 2018 In this paper we propose a PID-based control scheme for the automatic regulation of the neuromuscular blockade level during surgery. In particular, we introduce an optimized tuning of the PID controller parameters based on a standard set of patient models presented in literature. The tuning procedure is based on the solution of a min-max multiobjective optimization problem that takes into account the control performance, the control effort and the robustness. A genetic algorithm is used to solve the optimization problem and to find the optimal tuning. Then, in order to evaluate the control systems robustness, the optimal PID controller is tested in simulation on a database of patient models estimated from real data. The obtained results demonstrate that the performance achieved by considering an optimized PID tuning satisfies the clinical specifications and is robust to the inter-patient variability.